Study on the Kinetics of Calcium Metabolism with the Aid of 46Ca followed by Neutron Activation Analysis - Szymendera, J.; Sieniawska, M.; Lada, W.; Burzyńska, E.; Tołwiński, J.; Jasiński, W. K. (Nuklearmedizin - NuclearMedicine, 1967)
Paired kinetic studies in conjunction with balance studies of calcium were carried out in a child aged seven months before and after vitamin D. Stable 46Ca enriched to 6.48 mole per cent was used as tracer. Changes in 46Ca abundance in urinary and faecal calcium samples were determined by neutron activation analysis. Calculations of kinetic parameters of calcium metabolism were done by standard methods using a single-compartment model of calcium metabolism. This type of study does not subject the investigated child to any radiation dose, gives reliable results and seems to be the method of choice for solving problems of bone mineral metabolism in paediatrics.